PRESA LOCALĂ: ABORDĂRI FUNCȚIONALE - Toacă, Mariana (Academia de Știinițe a Moldovei, 2016)
Local media includes media institutions organized so that they disseminate public information horizontally, vertically and locally to ensure communication between social individuals, groups, social levels and classes that coexist in a given habitat. Local media represents an element of the printed mediawith distinct identity, its character emerges from its goals, roles and its functional particularities. The general role of local media is to strengthen the social space in a particular territory, usually equivalent to an administrative-territorial unit. The overall objective of local media is to provide flow of local information in accordance with national or even international information flow. To achieve this goal, local periodicals are performing a particular kind of media services and media activities which radically distinguish them from the national media.
LOCAL MEDIA: FUNCȚIONAL APPROACHES
Keywords: local media; targets; roles; creative potenti; human component; institutional component